Shooters Bible Guide to Firearms Assembly, Disassembly, and Cleaning, Vol. 2 - Sadowski, Robert A. (New York : Skyhorse Publishing, 2023)
If you liked Shooters Bible Guide to Firearms Assembly, Disassembly, and Cleaning Volume 1, youll love the Volume 2 with all new guns including popular shotguns, rifles, pistols, revolvers, and "other firearms." Plus, Volume 2 includes an expanded full-color section on a variety of DIY customization projects--from building an AR-15 build from a kit to adding ivory grips to your six-shooter. Each volume of the Disassembly series of books provides new guns and new DIY projects...
Keywords: Firearms -- Maintenance and repair